Chemokines in Chronic Liver Allograft Dysfunction Pathogenesis and Potential Therapeutic Targets. (8th December 2013) - Liu, Bin; Li, Jing; Yan, Lu-Nan
Abstract : Despite advances in immunosuppressive drugs, long-term success of liver transplantation is still limited by the development of chronic liver allograft dysfunction. Although the exact pathogenesis of chronic liver allograft dysfunction remains to be established, there is strong evidence that chemokines are involved in organ damage induced by inflammatory and immune responses after liver surgery. Chemokines are a group of low-molecular-weight molecules whose function includes angiogenesis, haematopoiesis, mitogenesis, organ fibrogenesis, tumour growth and metastasis, and participating in the development of the immune system and in inflammatory and immune responses. The purpose of this review is to collect all the research that has been done so far concerning chemokines and the pathogenesis of chronic liver allograft dysfunction and helpfully, to pave the way for designing therapeutic strategies and pharmaceutical agents to ameliorate chronic allograft dysfunction after liver transplantation.